1999
DOI: 10.1046/j.1365-3164.1999.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone resistance in Staphylococcus intermedius

Abstract: Four canine isolates of S. intermedius resistant to enro¯oxacin were isolated amongst a total of 429 screened. Two of these were shown to exhibit resistance also to marbo¯oxacin and cipro¯oxacin. Whilst molecular studies have shown the mechanism of resistance to these quinolone antibiotics to be similar in a number of staphylococcal species, it was not possible to con®rm this mechanism in Staphylococcus intermedius.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 9 publications
3
22
1
Order By: Relevance
“…This obser vation would explain the higher than expected resistance rate (5.7%) in the present in vitro study, reportedly mediated through mutations in the gyrA and/or nor A genes (Lloyd et al 1999).…”
contrasting
confidence: 40%
See 1 more Smart Citation
“…This obser vation would explain the higher than expected resistance rate (5.7%) in the present in vitro study, reportedly mediated through mutations in the gyrA and/or nor A genes (Lloyd et al 1999).…”
contrasting
confidence: 40%
“…Although enrofloxacin rarely induces bacterial resistance (Frank and Kunkle 1993, Pedersen and Wegener 1995, Lloyd et al 1999, we and other investigators (Scott 1997) have been experiencing a certain number of deep pyoderma cases that responded poorly to this medication, in contrast to cefalosporins. This obser vation would explain the higher than expected resistance rate (5.7%) in the present in vitro study, reportedly mediated through mutations in the gyrA and/or nor A genes (Lloyd et al 1999).…”
mentioning
confidence: 80%
“…In contrast to the data on human S. aureus strains, very little is known about the genetic basis of fluoroquinolone resistance in animal staphylococci. A study on 429 canine S. intermedius isolates obtained between 1996 and 1998 identified four resistant isolates [37]. Attempts to amplify the gyrA region -assumed to be involved in fluoroquinolone resistance -with the PCR primers known to be from S. aureus did not yield the expected amplification products in two resistant and two sensitive S. intermedius isolates as well as in a sensitive S. hyicus isolate [37].…”
Section: Resistance To Fluoroquinolonesmentioning
confidence: 99%
“…A study on 429 canine S. intermedius isolates obtained between 1996 and 1998 identified four resistant isolates [37]. Attempts to amplify the gyrA region -assumed to be involved in fluoroquinolone resistance -with the PCR primers known to be from S. aureus did not yield the expected amplification products in two resistant and two sensitive S. intermedius isolates as well as in a sensitive S. hyicus isolate [37]. This observation suggested that the gyrA genes from S. intermedius and S. hyicus differ in their sequences from those seen in S. aureus and more basic work is needed to identify mutations in the gyr and par genes possibly involved in fluoroquinolone resistance of animal staphylococci.…”
Section: Resistance To Fluoroquinolonesmentioning
confidence: 99%
“…The present treatment protocol for wounds supported each phase of the healing process, avoiding the need to use cytotoxic disinfectants (Noble & Kent 1992, Lloyd et al 1999, Rantala et al 2004, Paterson et al 2005, Lee et al 2006.…”
Section: Discussionmentioning
confidence: 99%